Blood circulating miR-28-5p and let-7d-5p associate with premature ageing in Down syndrome. (September 2022) - Morsiani, Cristina; Bacalini, Maria Giulia; Collura, Salvatore; Moreno-Villanueva, María; Breusing, Nicolle; Bürkle, Alexander; Grune, Tilman; Franceschi, Claudio; De Eguileor, Magda; Capri, Miriam
Abstract: Persons with Down syndrome (DS) undergo a premature ageing with early onset of age-related diseases. The main endpoint of this study was the identification of blood circulating microRNAs (c-miRs) signatures characterizing DS ageing process. A discovery phase based on array was performed in plasma samples obtained from 3 young (31 ± 2 years-old) and 3 elderly DS persons (66 ± 2 years-old). Then, a validation phase was carried out for relevant miRs by RT-qPCR in an enlarged cohort of 43 DS individuals (from 19 up to 68 years-old). A group of 30 non-trisomic subjects, as representative of physiological ageing, was compared. In particular miR-628–5p, miR-152–3p, miR-28–5p, and let-7d-5p showed a lower level in younger DS persons (age ≤ 50 years) respect to the age-matched controls. Among those, miR-28–5p and let-7d-5p were found significantly decreased in physiological ageing ( oldest group ), thus they emerged as possible biomarkers of premature ageing in DS. Moreover, measuring blood levels of beta amyloid peptides, Aβ-42 was assessed at the lowest levels in physiological ageing and correlated with miR-28–5p and let-7d-5p in DS, while Aβ-40 correlated with miR-628–5p in the same cohort. New perspectives in terms of biomarkers are discussed. Highlights: Blood miR-levels is lower in DS persons ≤ 50 years than age-matched controls. miR-28–5p and let-7d-5p as potential biomarkers of premature ageing in DS. Aβ-42 positively correlates with miR-28–5p and let-7d-5p in DS.